If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 4b + -7 Reorder the terms: 5 = -7 + 4b Solving 5 = -7 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 5 + -4b = -7 + 4b + -4b Combine like terms: 4b + -4b = 0 5 + -4b = -7 + 0 5 + -4b = -7 Add '-5' to each side of the equation. 5 + -5 + -4b = -7 + -5 Combine like terms: 5 + -5 = 0 0 + -4b = -7 + -5 -4b = -7 + -5 Combine like terms: -7 + -5 = -12 -4b = -12 Divide each side by '-4'. b = 3 Simplifying b = 3
| 1x+2y=172 | | 3y-12=13z-12 | | 500-5x=50+10x | | .66n+4=10 | | T/2=13/q | | 3/3/3/x=x/2 | | 3x-5+x-12= | | 16x-8+9x=-8-7x | | 4q-8=8 | | 3/3/3/x=0,5 | | 8-3(4x+5)=5 | | 5x-5=8x-17 | | x^2-40x+5.5=0 | | 700/x*35=450(x*15) | | x/9=2/6 | | 7(p+4)=9p+28 | | 5/7=?/35 | | 7s^2-567= | | Log(3x-4)-log(6x)=2 | | 23x+45y=4876 | | 2(2t-3)=2(3-2) | | B=3abx^2-5x | | 4.67+x=13.27 | | 2(m+3)+3(m+4)= | | ln(ln(x))=3 | | 10x-4+6-12x=8 | | 3(2x-5)=3(3-2) | | 3s^2+25s+42=0 | | 1+6n+-3=-14 | | 16x+13y=8 | | M*m-3m=18 | | -2x+3=-5x+6 |